The Epistemology of the Prophet Ibrahim's Tauhid: The Integration of Naqli-Aqli Evidence for the Formation of Rational Faith in Contemporary Islamic Education - Rully Agung Firmansyah; Ahsan Hakim (Jurnal Pendidikan Indonesia, 2026)
This research aims to analyze the epistemology of the Prophet Ibrahim's monotheism in the Qur'an and formulate it as the basis for the formation of rational faith in contemporary Islamic education. Different from previous studies that generally stop at the historical or moral dimension of Ibrahim's story, this study focuses on the pattern of integration of the naqli-aqli postulate in his argument and its operationalization in the form of a conceptual model of aqidah learning. The research uses a qualitative approach with a literature study method, focusing on three main series of verses: QS. Al-An'am: 76–79, QS. Al-Anbiya: 57–67, and QS. Al-Baqarah: 258, which is analyzed through classical tafsir with manhaj Ahlus Sunnah as well as Islamic aqidah and epistemological literature, which is analyzed using content analysis techniques. The results of the study show that the epistemology of the Prophet Ibrahim's monotheism not only affirms revelation as the authority of truth and reason as an instrument of istidlal as explained by many scholars, but more specifically, forms a cosmic-empiric-dialogical pattern of argument that can be transformed into the principles of learning aqidah: based on nash, activating reason, touching fitrah, and rejecting contradictions. The main contribution of this research lies in the formulation of a conceptual model of aqidah learning that is oriented towards rational faith: learners not only know what to believe, but also why and how to explain it argumentatively within the framework of revelation. Thus, this article does not merely repeat the general concept of the harmonization of reason and revelation, but offers a practical framework for the development of dialogical, argumentative, and relevant aqidah learning for the strengthening of students' rational faith in the midst of the challenges of secular rationality, liberalism, and religious pluralism in the context of contemporary Islamic education.